The Penyuluhan Diabetes Melitus Gestasional pada Ibu Prenatal di Poli Kebidanan Rsud Arjawinangun Kabupaten Cirebon - Yulianingsih, Nengsih; Priyanto, Priyanto; Ruswadi, Indra (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Gestational diabetes mellitus (GDM) is a carbohydrate intolerance disorder that occurs during pregnancy and has never been diagnosed as diabetes. GDM can only be detected at 24 weeks of pregnancy. The lack of knowledge of pregnant women about diabetes during pregnancy can increase the incidence of GDM which can have an impact on complications in subsequent pregnancies. The purpose of this community service is to increase the knowledge of pregnant women about GDM through health education activities at Arjavinangun Hospital, Cirebon. This activity is open to all pregnant women who want to visit the Obstetrics and Gynecology Department of Arjavinangun Hospital, Cirebon and participate in health education activities. The method used is to provide health education about GDM and measure the level of knowledge of participants before and after the intervention to determine changes in knowledge. Based on the results of the implementation of socially beneficial tasks, it can be ascertained that the knowledge of pregnant women about gestational diabetes has increased. Community service activities to increase participant knowledge through health education for pregnant women at risk of GDM are very effective in increasing the knowledge of pregnant women about the occurrence of GDM as an effort for early detection of GDM.